Nathaniel Neujahr: capstone - Neujahr, Nathaniel, artist (Colorado State University. Libraries, 2017)
The artist's statement: Through my studies at Colorado State University I have grown an appreciation for developing a process and style that is my own. Idea development and research is fundamental to problem solving any visual problem. While working through these fundamental ideas it is also important to be open to the organic flow of solutions. Experimentations will lead to unseen or un-thought of visual solutions and a gain in experience. All this can only happen if you stay true to your influences and styles. For me the land and environment is a great source of influence in my work. The everyday vernacular glance can yield an incredible about of inspiration. Being from Montana the mountainous lands of the west are in my veins. This in combination with refining observation gives me the passion to produce visual art and design. Much of my work you can see this at play with organic forms, earth tones, and subject matter. As a designer I am never finished learning or searching, which is nothing but exciting.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design